Simulasi Numerik Hot-Spot Stress dan Stress Concentration Factor pada Sambungan Tubular Sederhana T, Y, K, dan X - Nurman Pamungkas; Suheri Suheri; Nur Fitria Pujo Leksonowati (Politeknik Negeri Batam, 2021)
In offshore structures installation, tubular joints are commonly used. Tubular joints fabricated with welding processes often cause high hot-spot stress (HSS). High value of HSS and stress concentration factor (SCF) in tubular joints will reduce the service life of offshore structures due to fatigue loads. In this study simple tubular junctions T, Y, K, and X were used to obtain HSS and SCF through FEM simulation. The location of the maximum HSS under axial loading varied around the initial crown, in the In-Plane Bending (IPB) loading located after the second crown, while in the Out-of-Plane Bending (OPB) loading it was around the second saddle. In general, the SCF value in the three loading models from the FEM simulation is lower than SCF formula calculations in the previous study, these results are in line with recent SCF review study.